2007
DOI: 10.7498/aps.56.529
|View full text |Cite
|
Sign up to set email alerts
|

Enhanciement of exchange bias with diluted antiferromagnets in FM/AFM bilayers

Abstract: Based on Monte Carlo method, the characteristic of exchange bias is discussed in diluted antiferromagnets in FM/AFM bilayers by changing the dilute concentration. The simulation results show that the exchange bias in FM/AFM bilayers can be enhanced significantly by introducing nonmagnetic atoms into the AFM layers. And there is a maximum in the diagram of exchange bias as a function of the dilute concentration, i.e., the exchange bias at first increases then decreases with increasing concentration of dilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since the novel magnetic properties of EB are conducive to improve magnetic sensor and recording technologies effectively, the studys on the EB have recently attracted considerable interest in experiment and theory. For example, many authors have studied a variety of effects of the exchange bias, such as temperature [6,7], cooling field [8], interface exchange coupling constant [9], thickness [10,11], dopants and defects [12] as well as the antiferromagnetic dilution [13,14].Recently, the effect of interface magnetic dilution on exchange bias is studied with extensive Monte Carlo simulations for a model system consisting of a ferromagnetic layer exchange coupled to a diluted antiferromagnet [15]. It is found that the magnetic dilution and bond distribution of the ferromagnetic interface layer can lead to an increase in the bias field magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Since the novel magnetic properties of EB are conducive to improve magnetic sensor and recording technologies effectively, the studys on the EB have recently attracted considerable interest in experiment and theory. For example, many authors have studied a variety of effects of the exchange bias, such as temperature [6,7], cooling field [8], interface exchange coupling constant [9], thickness [10,11], dopants and defects [12] as well as the antiferromagnetic dilution [13,14].Recently, the effect of interface magnetic dilution on exchange bias is studied with extensive Monte Carlo simulations for a model system consisting of a ferromagnetic layer exchange coupled to a diluted antiferromagnet [15]. It is found that the magnetic dilution and bond distribution of the ferromagnetic interface layer can lead to an increase in the bias field magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, under the reversal of FM domains, the uncompensated grains or domains will be irreversibly reorganized [15−19] and thus cause the training effect. Although different models are adopted by some simulations [20,21] and theoretical investigation, [22−26] actual nonequilibrium dynamical properties of the magnetization are still waiting to be elucidated. It is highly desirable and needed to systematically investigate the two effects in a unified theory.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, molecular dynamics (MD) simulation [14] based on a coarse-grained bead-spring model is performed to examine the spreading process on solid substrates. Particularly, the hydrogen bonds among lubricant molecules and the hydrogen bonds between lubricant molecules and solid substrates are studied in detail.…”
Section: Introductionmentioning
confidence: 99%